PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP REAKSI INVESTOR - Rosida, Alisa; Fitria, Astri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to analyze how the influence of company financial performance which is focused on return on investment (ROI), return on equity (ROE), net profit margin (NPM), earnings per share (EPS), price book value (PBV) and firm size to the abnormal return. The population is the property and real estate companies which are listed in Indonesia Stock Exchange in 2011-2014 periods, these companies have been selected by using purposive sampling and it is based on the determined criteria, so 17 companies have been selected as samples. The analysis method has been done by using multiple linear regressions analysis, hypothesis test i.e. coefficient determination, F test, t test. Based on the result of multiple regressions analysis and the t test with the significance level is 5% so the result of the result shows that partially the financial performance (return on investment (ROI), return on equity (ROE), earning per share (EPS), price book value (PBV) and firm size have significant influence to the abnormal return. Meanwhile, the financial performance (net profit margin NPM) does not have any significant influence to the abnormal return. It indicates that investors always perform analysis in making investment decision in order to obtain more accurate data in conducting investment which has been done by conducting technical and fundamental analysis. Therefore, the financial performance becomes one of the considerations for prospective investors to invest their capital. Keywords: Financial Performance, Firm Size, Abnormal Return.